Improving Reading Comprehension in English for Nusantara: A Case Study - Syahid, Abdul; Anggraini, Aprillia; Hafizah, Azizatun; Ikrimah, Ikrimah; Nadia, Nadia (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
This research investigates the effectiveness of using the textbook "English for Nusantara" for grade 7, to improve reading comprehension skills among students at Al-Amin Middle School in Palangka Raya City, Indonesia. This research uses a qualitative approach, utilizing questionnaires and student interviews to analyze how textbooks facilitate reading comprehension. This research focuses on a sample of 10 students and aims to identify the strengths and the content of "English for Nusantara" textbook in improving reading comprehension. This analysis will explore four main aspects: general attributes, teaching-learning content, vocabulary development, and grammatical understanding. The findings from this research will provide valuable insight the potential to be an effective tool for enhancing reading comprehension and the content of the book "English for Nusantara" from the views of Al-Amin Palangkaraya Middle School students and contribute to the ongoing dialogue about effective teaching of reading comprehension in secondary schools in Indonesia.